1972
DOI: 10.1136/pgmj.48.559.308
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive iodine (131I) therapy for thyrotoxicosis at Groote Schuur Hospital over a 6-year period

Abstract: SummaryThe case records of 262 patients who received 131l therapy during a 6-year period were analysed retrospectively. These included seventy-eight patients who received more than one therapeutic dose.The major indication for 131I therapy was thyrotoxicosis occurring in patients aged 40 years and over.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In our patient, RAI therapy with only 6 mCi led to postablative hypothyroidism in 2002 but within a few months to hypocalcemia from hypoparathyroidism (November 2001) which is unusual. The percentage of patients who became hypothyroid post RAI therapy at a similar irradiation dose (6 mCi) as our patient was 21% in one study, while another study showed transient decline in PTH levels over time (6,20). (22,23).…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…In our patient, RAI therapy with only 6 mCi led to postablative hypothyroidism in 2002 but within a few months to hypocalcemia from hypoparathyroidism (November 2001) which is unusual. The percentage of patients who became hypothyroid post RAI therapy at a similar irradiation dose (6 mCi) as our patient was 21% in one study, while another study showed transient decline in PTH levels over time (6,20). (22,23).…”
Section: Discussionmentioning
confidence: 44%
“…The percentage of patients who became hypothyroid post RAI therapy at a similar irradiation dose (6 mCi) as our patient was 21% in one study, while another study showed transient decline in PTH levels over time (6,20). Glazebrook et al (21) investigated prospectively the relations between RAJ therapy (high doses) and secondary hypoparathyroidism and postulated a possible compromised parathyroid reserve prior to the inflicting event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be borne in mind however that mild hypothyroidism may be temporary following thyroidectomy (Toft et al , 1976), and the diagnosis of permanent hypothyroidism should not be made with confidence until 6 months have elapsed after partial thyroidectomy. Temporary hypothyroidism has also been described after treatment with I 131 (Sagel et al , 1972).…”
Section: Aetiologymentioning
confidence: 99%